Produtos proteicos de oxidação avançada (AOPPs) agem como agonistas do receptor TRPA1 interferindo na fisiopatologia da esclerose múltipla - Rodrigues, Patricia (2024)
Multiple sclerosis (MS) is divided into four forms: clinically isolated syndrome (CIS), relapsing-remitting MS (RRMS), secondary progressive MS (SPMS), and primary progressive MS (PPMS). This disease is characterized by oxidative imbalance, with symptoms of neuropathic pain and anxiety. In experimental models, nociception, neuroinflammation, and demyelination have been associated with the activation of the transient receptor potential ankyrin 1 (TRPA1). TRPA1 gene deletion reduces neuroinflammation and demyelination in experimental autoimmune encephalomyelitis (EAE) models. However, no TRPA1 antagonists are currently available in clinical practice or clinical trials. Advanced oxidation protein products (AOPPs) are being investigated in clinical trials due to their involvement in the physical disability of MS patients. Despite this, there are no systematic reviews and meta-analyses evaluating the role of AOPPs in MS pathophysiology, as well as nociceptive and anxiety-like mechanisms in animal models. We aimed to conduct a systematic review and meta-analysis to assess the involvement of AOPPs in MS pathophysiology and to verify the mechanisms of action of these compounds on nociception, neuroinflammation, demyelination, and anxiety-like behavior in EAE models in female mice. In the systematic review and meta-analysis, we observed an increase in AOPP concentrations related to greater physical disability in MS patients. In the progressive EAE model (PMS-EAE), AOPP levels were elevated in central nervous system structures and correlated with cold allodynia and anxiety index. Next, we found that AOPPs selectively activate TRPA1, resulting in nociception. In the relapsing-remitting EAE model (RR-EAE), treatment with apocynin (100 mg/kg, orally) reduced AOPP levels, nicotinamide adenine dinucleotide phosphate oxidase (Nox) and myeloperoxidase (MPO) activation, nociception, anxiety-like behavior, neuroinflammation, and demyelination. Acute injection of anti-AOPP antibody (5 µl/site, intrathecally) showed antinociceptive and anxiolytic effects in both the RR-EAE model and AOPP-induced nociception by intrathecal administration of AOPPs (10 nmol/site). Correlations indicated the activation of the AOPP production pathway through increased Nox activity and induction of neuropathic and anxiety-like behaviors due to neuroinflammation generated by TRPA1 activation. These findings highlight therapeutic approaches for managing neuroinflammation, anxiety-like behaviors, and neuropathic pain in EAE models by reducing AOPPs that act as TRPA1 agonists.